2018
DOI: 10.1037/fam0000467
|View full text |Cite
|
Sign up to set email alerts
|

A two-way street: Mothers’ and adolescent daughters’ depression and PTSD symptoms jointly predict dyadic behaviors.

Abstract: Dyadic interactions may be affected by the mental health of either partner; however, both partners’ symptoms are typically not considered simultaneously in observational studies of parent-child relationships. Using the Actor Partner Interdependence Model (APIM), we examine how depression and PTSD symptoms in mothers and adolescent daughters predict their own and each other’s relational behaviors (warmth, hostility, communication) during interactions, and whether partners’ relational behaviors predict changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
0
17
3
Order By: Relevance
“…The posteriors resulting from the logarithmic pooled priors were spiked and highly driven by the previous information as confirmed by the low associated shrinkage. In the current study, two studies (i.e., Pinquart, 2017 ; Milan and Carlone, 2018 ) caused all spikes. These studies reported estimates with extremely small (standardized) standard errors, thus strengthening the evidence for these effects.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The posteriors resulting from the logarithmic pooled priors were spiked and highly driven by the previous information as confirmed by the low associated shrinkage. In the current study, two studies (i.e., Pinquart, 2017 ; Milan and Carlone, 2018 ) caused all spikes. These studies reported estimates with extremely small (standardized) standard errors, thus strengthening the evidence for these effects.…”
Section: Discussionmentioning
confidence: 50%
“…These studies reported estimates with extremely small (standardized) standard errors, thus strengthening the evidence for these effects. While Pinquart (2017) conducted a longitudinal meta-analysis on the associations between parental behaviors and adolescent internalizing symptoms with over 1,000 included studies, Milan and Carlone (2018) investigated actor and partner effects in how mother and adolescent internalizing symptoms predicted maternal and adolescent behaviors during an interaction task. Both studies provide important information for our analyses, but do not precisely reflect our study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, adolescent-reported maternal negative affect was related to concurrent adolescent internalizing and externalizing symptoms (Stocker et al, 2007). Previous studies further indicated that maternal positive affect was associated with positive functioning, including prosocial behavior (Michalik et al, 2007) and social competence (Eisenberg et al, 2001), in (early) childhood as well as fewer problem behaviors in childhood (Cumberland-Li et al, 2003;Eisenberg et al, 2001;McCoy & Raver, 2011) and adolescence (Milan & Carlone, 2018). Generally, these studies suggest that higher levels of maternal negative affect and lower levels of maternal positive affect contribute to adolescent psychopathological symptoms.…”
Section: Maternal Affect and Adolescent Psychopathologymentioning
confidence: 90%
“…Recently, with in‐depth exploration of the Theory of Dyadic Illness Management, APIM is increasingly applied to estimate inherent interdependence between dyadic ones in different situations. Cross‐sectional and longitudinal research all indicated children's emotion and parents' perception of children were connected and interacted with their physiological and psychological states (Fagan & Palkovitz, 2019; Han & Lee, 2020; Jeong & Hun‐Ha, 2020; Milan & Carlone, 2018). However, interaction of QoL and perspective of children's transition readiness concerning dyadic phenomena between parent–child relationships are rarely considered relevant.…”
Section: Introductionmentioning
confidence: 99%